2019
DOI: 10.2196/10930
|View full text |Cite
|
Sign up to set email alerts
|

Research-Tested Mobile Apps for Breast Cancer Care: Systematic Review

Abstract: Background The use of mobile health (mHealth) apps in clinical settings is increasing widely. mHealth has been used to promote prevention, improve early detection, manage care, and support survivors and chronic patients. However, data on the efficacy and utility of mHealth apps are limited. Objective The main objective of this review was to provide an overview of the available research-tested interventions using mHealth apps and their impact on breast cancer care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
132
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 45 publications
6
132
0
Order By: Relevance
“…As smartphone usage increases, new interventions may need to be specifically designed for mobile devices rather than relying on responsive web designs that are not fully adaptive to all smartphones. However, adoption of mobile self‐management apps by people with cancer has been limited to date, and there is limited evidence regarding their efficacy in improving psychological outcomes …”
Section: Discussionmentioning
confidence: 99%
“…As smartphone usage increases, new interventions may need to be specifically designed for mobile devices rather than relying on responsive web designs that are not fully adaptive to all smartphones. However, adoption of mobile self‐management apps by people with cancer has been limited to date, and there is limited evidence regarding their efficacy in improving psychological outcomes …”
Section: Discussionmentioning
confidence: 99%
“…(5) To test whether the use of OWise reduces the rate of resource utilization in the first year following diagnosis compared to standard care among patients registered in Discover, an integrated health and social care record in North West London. (6) To test whether the use of OWise reduces the average cost per patient in the first year following diagnosis compared to standard care among patients registered in Discover. 7To describe the change in patient activation in the intervention group compared to the control group in the first year following diagnosis.…”
Section: Secondary Objectivesmentioning
confidence: 99%
“…mHealth is the application of mobile technology by patients or health care providers to monitor health and improve outcomes [5]. A recent review has found 12 studies assessing mHealth tools to support self-management in breast cancer patients [6]. Many of the studies assessing mHealth tools found promising results with a wound monitoring application reducing health resource utilization [7], an electronic daily journal stabilizing daily functional activity [8] and an application providing information and support improving selfefficacy and quality of life and reducing symptom interference [9].…”
Section: Introductionmentioning
confidence: 99%
“…Model-based intervention supports planners in recognizing theoretic structures to consider in an intervention to extract behavioral modi cation (40,41). Furthermore, the theoretic basis offers an approach to smartphone preventive behavior intervention improvement (42).…”
Section: Introductionmentioning
confidence: 99%